2016
DOI: 10.1021/acs.biomac.6b01243
|View full text |Cite
|
Sign up to set email alerts
|

Nanocellulose-Based Interpenetrating Polymer Network (IPN) Hydrogels for Cartilage Applications

Abstract: Double cross-linked interpenetrating polymer network (IPN) hydrogels of sodium alginate and gelatin (SA/G) reinforced with 50 wt % cellulose nanocrystals (CNC) have been prepared via the freeze-drying process. The IPNs were designed to incorporate CNC with carboxyl surface groups as a part of the network contribute to the structural integrity and mechanical stability of the hydrogel. Structural morphology studies of the hydrogels showed a three-dimensional (3D) network of interconnected pores with diameters in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(111 citation statements)
references
References 52 publications
6
105
0
Order By: Relevance
“…The scaffolds were printed in dimensions of 2 × 2 × 2 cm 3 with pore size of 1 mm and pore wall thickness of 0.5 mm ( Figure ). Additional polymers (e.g., alginate) and divalent cations (Ca 2+ ) were used to stabilize the 3D printed structures through fast ionic crosslinking . The ZIF‐8 loading, up to a certain limit, improved the rheological properties (Figure ).…”
Section: Resultssupporting
confidence: 81%
“…The scaffolds were printed in dimensions of 2 × 2 × 2 cm 3 with pore size of 1 mm and pore wall thickness of 0.5 mm ( Figure ). Additional polymers (e.g., alginate) and divalent cations (Ca 2+ ) were used to stabilize the 3D printed structures through fast ionic crosslinking . The ZIF‐8 loading, up to a certain limit, improved the rheological properties (Figure ).…”
Section: Resultssupporting
confidence: 81%
“…We have reported in the recent years scaffolds, implants and wound dressing materials based on nanocellulose and nanochitin as reinforcements in biopolymers prepared via casting, electrospinning or freeze-drying processes. [5][6][7][8][9] These studies demonstrated nanostructured and cytocompatible scaffolds with high porosity, nanoscaled pore wall roughness, pore interconnectivity and wet mechanical properties suitable for biomedical applications. However, an accurate control of the pore sizes was not achieved through these processing techniques.…”
Section: Introductionmentioning
confidence: 88%
“…Aarstad et al 91 prepared CaCO 3 /D-glucono-δ-lactone modified alginate hydrogels containing CNFs and cross-linked with CaCl 2 that showed a high elastic modulus value. Naseri et al 92 developed double-network hydrogels with alginate and gelatin also containing 50% CNCs. The hydrogel presented an elastic modulus value of 0.5 GPa, a mechanical strength of 14.4 MPa and a deformation of 15.2%.…”
Section: Alginatementioning
confidence: 99%